Media Sosial, Endorsement, dan Micro Influencer: Konsep Integrated Marketing Communication - Adhi Gurmilang; Irwan Setyawan; Arifah Armi Lubis; Siti Khopipah; Kartika Ariyani (Ilmu Komunikasi, 2026)
Abstract - Abstracts are written briefly and factually briefly stated research objectives, main results and main conclusions. Abstracts are often presented separately from the article, so it should be able to stand alone. Therefore, references should be avoided, but if necessary, the quotation must be complete. Non-standard or unusual abbreviations should be avoided, but if necessary it should be defined in their first mention in the abstract itself. Abstracts are written in italic, space 1, size 11, Font Book Antiqua also include keywords. The number of words for abstract is min. 150-200 words, which contains problems, goals, methods, and results. While the keywords maximum of five words that reflect the contents of the script. Immediately after the abstract, provide a maximum of five keywords, avoid general and plural terms and many concepts (avoid, for example, 'and', 'from'). Efficient with abbreviations: only abbreviations are defined in the eligible field. This keyword will be used for indexing purposes.